Bridging the University Funding Gap: Determinants and Consequences of University Seed Funds and Proof-of-Concept Programs in Europe - Federico Munari; Maurizio Sobrero; Laura Toschi (European Investment Fund (EIF), 2015)
The limited availability of private funding sources to support technology transfer activities represents a major barrier to the effective commercialization of university technologies. This working paper analyzes the key determinants of use of financial instruments by universities - such as seed funds and proof-of-concept programs - to address such funding gaps. Using data from a survey of technology transfer office managers in European universities, the authors detail the antecedents of the presence of such instruments at the university level and their perceived effectiveness. The findings in turn have notable policy implications.
Keywords: 330; Funding gap; university seed funds; proof-of-concept programs; technology transfer